The politics of domestic energy vulnerability in the Barcelona region, between deconfinement and reconfinement. Issue 116 (November 2020) - Desvallées, Lise; Coutard, Olivier; Rutherford, Jonathan
Abstract: This paper studies the diverse actions, interventions and strategies initiated to address rising energy vulnerability among low-income households in the Barcelona region over the last decade. Drawing upon recent conceptual work around the politics of energy and in-depth fieldwork conducted over more than two years, we trace the different processes and sites through which the basic socio-material conditions of domestic access to energy have become politicised. We show how this involves a two-stage movement of deconfinement and reconfinement. In a context marked by austerity, an energy inefficient urban fabric and a centralised and oligopolistic energy system, energy vulnerability emerged from the domestic and private sphere to become framed as a public problem through parliamentary debate, social protest and local authority initiatives. Yet, energy access and vulnerability have also to some extent been recontained in the space of the household through the focus of recent local policy intervention on 'low cost' measurement, audit and equipment of domestic energy use. We argue that in reprivatizing what had become a public issue and thus redistributing responsibility for change to the household level, authorities and practitioners continue to ignore the systemic factors behind energy vulnerability situations and reproduce a status quo that benefits only energy utilities. The contribution of the paper is thus to show a politics of energy access that is increasingly constituted through entangled, fluid, blurred forms of relations between domestic and collective issues. This politics allows, for example, the need for systemic change to be framed as ostensibly a concern of households and to be met through fragmented, low-cost, metrological measures at that level.